Menyingkap Keagungan Karakter Rut dari dalam Bayang-Bayang: Penerapan Analisis Tokoh dalam Narasi Kitab Rut - Sia, Kok-Sin (Veritas : Jurnal Teologi dan Pelayanan, 2021)
Uncovering the Noble Character of Ruth out of Shadows: Applying Character Analysis in the Book of Ruth. This article is an effort to apply the character analysis in the book of Ruth that shows the excellence of Ruth and the response of the original readers. Character analysis was carried out using the method of Richard L. Pratt Jr., which includes the description of characterizations, characterization techniques, and characterization purposes, to investigate the characters of Naomi, Ruth, and Boaz as the three main characters in this book. These three characters are analyzed and compared to find the purpose of characterization and the reader’s response. Through this analysis, we can find that the author of the book of Ruth has a purpose to describe indirectly or subtly the noble character of Ruth in the shadows of her background as a Moabites and the other main characters, Naomi and Boaz. Through the reading of the book of Ruth, the first readers can evaluate their spirituality as God’s people because they find that there is a Moabite woman whose life is godlier than them. It also raises awareness that Israel’s God embraces all nations and that non-Israelites do not always negatively influence God’s people.